2018
DOI: 10.3390/ijms19123940
|View full text |Cite
|
Sign up to set email alerts
|

The Multifaceted Roles of Autophagy in Flavivirus-Host Interactions

Abstract: Autophagy is an evolutionarily conserved cellular process in which intracellular components are eliminated via lysosomal degradation to supply nutrients for organelle biogenesis and metabolic homeostasis. Flavivirus infections underlie multiple human diseases and thus exert an immense burden on public health worldwide. Mounting evidence indicates that host autophagy is subverted to modulate the life cycles of flaviviruses, such as hepatitis C virus, dengue virus, Japanese encephalitis virus, West Nile virus an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 520 publications
(783 reference statements)
1
43
0
Order By: Relevance
“…One is to be involved in the assembly and release of the virus by its membrane trafficking character. The other is to adjust the host antiviral immune response [48]. In this study, we found that autophagy inhibition with knockdown of Beclin 1 and LC3B increased the mRNA levels of Type I interferons and IL-6 ( Figure 5A) and also enhanced IRF7 and NF-κB promoter activation ( Figure 5B).…”
Section: Discussionmentioning
confidence: 58%
“…One is to be involved in the assembly and release of the virus by its membrane trafficking character. The other is to adjust the host antiviral immune response [48]. In this study, we found that autophagy inhibition with knockdown of Beclin 1 and LC3B increased the mRNA levels of Type I interferons and IL-6 ( Figure 5A) and also enhanced IRF7 and NF-κB promoter activation ( Figure 5B).…”
Section: Discussionmentioning
confidence: 58%
“…Multiple evidence has indicated that autophagy plays an important role in flavivirus infection (Ke, 2018). But there are rare reports on the effect of autophagy on virus replication in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Altered lipid metabolism is linked to the life cycle of HCV considering that virions coated with lipoproteins facilitate hepatocyte entry via lipoprotein receptors, however, the HCV-induced ER-stress leads to steatosis [3]. Intracellular lipid droplets being in excess in the cells are degraded by an autophagy process called lipophagy [3][4][5]22]. Vescovo et al reported that autophagy acts against the alterations in lipid metabolism induced by HCV and steatosis may develop when autophagy is disrupted [39].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the remarkable healing effect of the newly introduced direct-acting antivirals (DAAs), several issues are still not resolved or are under dispute [2,3]. One of these is the role autophagy may play in the pathogenesis of chronic hepatitis C (CHC), which has been in the focus of several recent studies [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation